EXPLORING PRE-SERVICE TEACHER’S CODE-SWITCHING PRACTICE IN EFL CLASSROOM: A CASE STUDY IN LEARNING WRITING - Putri Fitriani Khairunnisa; Yogi Setia Samsi (IKIP Siliwangi, 2023)
In the EFL class, the use of code switching plays an important role in delivering teacher's utterances to easily understand by linking English and Indonesian. This article explores the use and functions of code switching practice towards pre-service teacher’s utterances in EFL classroom. The research focused on functions and pre-service teacher perception of code switching in EFL classroom. Using data from pre-service English teacher's verbatim in one-on-one interview recording and classroom observation, this study uncovered how EFL pre-service teacher used code switching with several situations. The results exposed that switching topic, affective, and repetitive functions do exist in learning writing in language practice. The research also identified three major purposes is applied in learning writing; questioning and asking, explaining and giving instuctions, and translating functions.